Motivating, Learning, Performance, and Persistence The Synergistic Effects of Intrinsic Goal Contents and Autonomy-Supportive Contexts . [article]. - Vansteenkiste, Maarten
Three fields experiments with high school and college students tested the self-determination theory (E. L. Deci & R. M. Ryan, 2000) hypotheses that intrinsic (vs. extrinsic) goals and autonomy-supportive (vs. controlling) learning climates would improve students' learning, performance, and persistence. The learning of text material of physical exercises was framed in terms of intrinsic (community, personal growth, health) versus extrinsic (money, image) goals, which were presented in an autonomy-supportive versus contolling manner. Analyses of variance confirmed that both experimentally manipulated variables yielded main effects on depths of processing, test performance, and persistence (all ps <.001). and an interaction resulted in synergistically high deep processing and test performance (but not persistence) when both intrinsic goals and autonomy support were present. Effects were significantly mediated by autonomous motivation. (from the author)